JENIS FRASA DAN MODUS DALAM NADZAM AL-MANDZUMAH AN-NAWAWIYYAH WA AL-KHASAIS AN-NAHDLIYAH KARYA K.H. ZULFA MUSTOFA - Rino, Rino; Supriadi, Dedi (Hijai - Journal on Arabic Language and Literature, 2023)
The purpose of this study  is to know the types of phrases contained in material objects  , namely nadzam Al-Manẓumah An-Nawawiyyah Wa Al-Khasā'is An-Nahḍiyyah and to know the type of mode contained in these objects. In his discussion, researchers borrowed the theory proposed by Abdul Chaer, namely the categorization of phrases into four types, including exocentric, endocentric, coordinative and apositive phrases. In addition, Abdul Chaer also divided the mode into seven types, including indicative (declarative), optative, imperative, interrogative, obligative, desiderative and conditional modes.  The method used is a descriptive qualitative method.  The results of this study describe a number of phrases and modes found in material objects, including: (1) The phrases contained in this material object are 187 with 64 endocentric types, 98 exocentric types, 22 coordinate types and 3 apositive types. (2) The modes contained in this material object are 50 with 42 declarative types, one optative type, six imperative types and one conditional type. Tujuan dari penelitian ini yang antara lain mengetahui jenis frasa yang terdapat dalam objek material yaitu nadzam Al-Manẓumah An-Nawawiyyah Wa Al-Khasā’is An-Nahḍiyyah serta mengetahui jenis modus yang terdapat dalam objek tersebut. Dalam pembahasannya peneliti meminjam teori yang dikemukakan oleh Abdul Chaer yaitu pengkategorian frasa menjadi empat jenis, antara lain frasa eksosentrik, endosentrik, koordinatif dan apositif. Selain itu Abdul Chaer juga membagi modus ke dalam tujuh jenis antara lain modus indikatif (deklaratif), optatif, imperatif, interogatif, obligatif, desideratif dan kondisional. Adapun metode yag digunakan adalah metode kualitatif deskriptif. Hasil dari penelitian ini memaparkan sejumlah frasa dan modus yang tedapat pada objek material antara lain: (1) Frasa yang terdapat dalam objek material ini berjumlah 187 dengan 64 jenis endosentrik, 98 jenis eksosentrik, 22 jenis koordinatif dan 3 jenis apositif. (2) Modus yang terdapat dalam objek material ini berjumlah 50 dengan 42 jenis deklaratif, satu jenis optatif, enam jenis imperatif dan satu jenis kondisional.